Facile synthesis of dual-morphological MgCo2O4 with remarkable performance for pseudosupercapacitors. Issue 1 (21st November 2022) - Ni, Hang; Ke, Zunjie; Hu, Tanwei; Liu, Wanneng; Tian, Yu; Zhu, Xiaolong; Zheng, Guang
Abstract : Dual-morphological MgCo2 O4 can be successfully synthesized on Ni foam via a simple hydrothermal route and it possesses a long-term cycle durability, giving power to LED for 24 min. Abstract : The facile preparation of electrode materials with superior capacitance can be rationally regarded as a fast and efficient strategy to improve the electrochemical properties of supercapacitors. In this work, dual-morphological MgCo2 O4 (DMCO) was successfully synthesized on Ni foam (NF) through a simple hydrothermal route. Honeycomb-like and urchin-like MgCo2 O4 was clearly observed by scanning electron microscopy (SEM) characterization of DMCO, which exhibited an excellent specific surface area of 100.62 m 2 g −1 . The as-prepared DMCO was tested in 2 M KOH electrolyte solution using a standard three-electrode system, and the results showed that DMCO exhibited a superior specific capacitance of 1552.34 F g −1 at the current density of 1 A g −1 . After 5500 cycles under the condition of 15 A g −1, 110% of the initial capacitance was retained when it is used as a binder-free electrode material for supercapacitors. Additionally, a DMCO//AC asymmetric supercapacitor (DMCO//AC ASC) was assembled with DMCO as the binder-free positive electrode and active carbon (AC) as the negative electrode, which displayed a high energy density of 27.46 W h kg −1 at a power density of 825.9 W kg −1, and a yellow light-emitting diode could remain lit for 24 min. The cycling performance of DMCO//AC ASC was investigated at the current density of 8 A g −1, where 98.8% of its initial capacitance was retained after 11 000 cycles, which undoubtedly demonstrates its outstanding and prolonged cycle stability. These remarkable electrochemical performances strongly verify that DMCO possesses great potential as a promising material for energy storage.